2014
DOI: 10.1002/eji.201343967
|View full text |Cite
|
Sign up to set email alerts
|

Human regulatory T cells are selectively activated by low‐dose application of the CD28 superagonist TGN1412/TAB08

Abstract: CD28 superagonists (CD28SAs) are potent T-cell-activating monoclonal antibodies (mAbs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 45 publications
5
74
0
2
Order By: Relevance
“…13 Membranes were probed with rabbit anti-human FcgRIIb (Abcam) and goat anti-rabbit IgG horseradish peroxidase (HRP) F(ab9) 2 , and the signal was visualized by using enhanced chemiluminescence (GE Healthcare Life Sciences).…”
Section: Western Blotmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Membranes were probed with rabbit anti-human FcgRIIb (Abcam) and goat anti-rabbit IgG horseradish peroxidase (HRP) F(ab9) 2 , and the signal was visualized by using enhanced chemiluminescence (GE Healthcare Life Sciences).…”
Section: Western Blotmentioning
confidence: 99%
“…There has been a keen focus on the development of therapeutic anti-CD28 mAbs for a range of diseases, including autoimmunity and cancer. [1][2][3] However, anti-CD28 mAbs suffered a major setback when the first-in-man trial of TGN1412 caused life-threatening CRS.…”
Section: Introductionmentioning
confidence: 99%
“…30 Interestingly, recent data suggest that CD28SA-activated and -expanded human Treg are very potent suppressors of inflammatory cytokine release in PBMC cultures from patients with rheumatoid arthritis. 34 The same study also showed that slow infusion of much lower doses (≤7 μg/kg) than used in the ill-fated HV trial of 2006 (bolus injection of 100 μg/kg) is well tolerated and leads to systemic release of IL-10 but not of proinflammatory cytokines. Further studies in different indications are needed to determine whether transient polyclonal Treg activation could be a safe and effective approach for stroke and other indications.…”
Section: Strokementioning
confidence: 88%
“…The WBCA is therefore not considered to be predictive of the clinical severity of adverse effects of mAb therapeutics and not suitable for ranking the risk, but is rather a tool for hazard identification. The severity of CRS could be decreased by an appropriate dosage regimen (Hale et al, 2004;Tabares et al, 2014) or by medication with anti-inflammatory agents (Lee et al, 2014). We considered that the WBCA is able to detect the potential of severe CRS occurring with high frequency in the worst case.…”
Section: Discussionmentioning
confidence: 99%